Association between cannabis use and sexual behavior among adolescents aged 12–15 years in 21 low- and middle-income countries. (December 2019) - Smith, Lee; Jackson, Sarah E.; Jacob, Louis; Grabovac, Igor; Nisbet, Lorna A.; López-Sánchez, Guillermo F.; McDermott, Daragh; Salmeron, Alejandro Gil; Yang, Lin; Koyanagi, Ai
Abstract: Aims: To investigate the relationship between cannabis use and two sexual behaviors (ever had sex, multiple partners) in a large representative sample of adolescents aged 12–15 years from 21 low- and-middle income countries. Methods: Data from 84, 867 adolescents aged 12–15 years participating in the Global School-based Student Health Survey were analyzed. Participants reported lifetime frequency of cannabis use (analyzed as 0, 1–2, 3–19 or ≥ 20 times), whether they had ever had sexual intercourse (yes/no) and, if yes, their lifetime number of sexual partners. We used multivariable logistic regression to analyze associations, adjusting for a range of relevant covariates. Results: 12.7% of the sample reported having had sexual intercourse, and of these adolescents, 53.1% had had multiple sexual partners. The prevalence of lifetime cannabis use of 1–2 times, 3–19 times, and ≥ 20 times were 1.1%, 1.2%, and 0.4%, respectively. Those who reported using cannabis 1–2 times, 3–9 times, and ≥ 20 times had 2.32 (95%CI = 1.47–3.65), 2.34 (95%CI = 1.34–4.07), and 5.45 (95%CI = 2.22–13.40) times higher odds of having had sexual intercourse than those who had never used cannabis. Among those who had ever had sexual intercourse, the respective odds ratios (95%CIs) for having multiple sexual partners were 1.56 (0.93–2.62), 1.70 (0.92–3.14), and 5.66 (2.97–10.82). There were no significant interactions by sex for these associations. Conclusions: Adolescents from LMIC who use cannabis are more likely to have ever had sexual intercourse than those who do not. Among those who have had sexual intercourse, those who use cannabis are more likely to have had multiple sexual partners. Highlights: Young adolescents who use cannabis are more likely to have ever had sexual intercourse than those who do not. Moreover, those who use cannabis are more likely to have had multiple sexual partners. These potential risks should be taken into consideration during debates around legalization of recreational cannabis use.